Spatial distribution of anemochorics and zoochorics taxons in Araucaria Forest fragments - Silva, Richeliel Albert (2019)
The present study had as objective to analyze the spatial pattern of the anemocoric and zoocoric species in environments with different individuals densities. The study was conducted in two fragments of Highland Araucaria Forest: one under silvipastoril system and another in a forest under secondary succession, in the municipality of Turvo, Paraná State, Brazil. The coordinates (x, y) of each point was registered. The spatial pattern was analyzed through the function K of Ripley, in the univariate form, using the package Splancs. In the area under silvipastoril system, anemochory syndrome is aggregated, while individuals with zoochory dispersion syndrome showed aggregated pattern up to 15 m and random pattern in the upper classes. Anemocoric species showed aggregated pattern in the area under secondary succession regardless the distance. Probably, more complex factors, such as dispersers´ ecology, interspecific relationships and environmental features may define the spatial distribution of some species.